The Effect of Inflation and MSME Production Growth on GDP with Fintech as an Intervening Variable: Study in Indonesia During the 2019-2022 Covid19 Pandemic - Rahmadi, Ferddy; Saefullah, Kurniawan; Anwar, Mokhamad (Jurnal Riset Ilmu Ekonomi, 2023)
The Covid-19 pandemic has significantly accelerated digitalization in Indonesia, particularly in the Fintech sector. Fintech, which focuses on Micro, Small, and Medium Enterprises (MSME), has experienced rapid growth during the pandemic. This study analyses the impact of inflation, MSME production growth, and the role of Fintech on GDP. The research uses a quantitative approach known as analytical descriptive research to gain a comprehensive understanding with four variables which are observed. The data was compiled by offiacial resources, such as Bank Indonesia, Indonesia Statistic Bureau, and Finance Services Authority. The results indicate that inflation has a significant positive effect, while MSME production growth is positive but insignificant. Furthermore, Fintech positively and significantly contributes to the Gross Domestic Product (GDP). Fintech can be optimized to increase MSME production growth and GDP, even though it does not mediate between inflation and GDP.